Analysis and control of linear systems (ISTE, 2007)
This work collects research on the theory of continuous-state automated systems whose inputs, outputs, and internal variables, such as temperature and speed, can vary in a continuous manner. Part I looks at control of signals and linear systems, with chapters on input-output and state representations, discrete time systems, structural properties of linear systems, deterministic and statistical models of signals, and the fundamental theoretical tools of state stabilization and estimation. Part II overviews the different approaches to control, with chapters on analysis and synthesis by classic monovariable techniques, predictive control, and automatic control engineering. A final chapter covers linear time- variant systems.